The Dual Ethical Dimensions of “Tian” in Xizi-Belief: Unveiling Tianming and Tianli Through a Hunan Case Study - Xin Zhang; Lei Liao; Xubin Xie (Religions)
This study focuses on Xizi-belief (惜字信仰) and provides a comparative analysis of the religious philosophies of Tianming (天命) and Tianli (天理), using the Hunan region as a case study. Through anthropological methods and fieldwork, this study explores how Classical Confucianism, Taoism, and Buddhism shape and guide word-cherishing behaviors based on the conceptual philosophies of Tianming and Tianli. The Tianming conception views characters as revelations of heavenly destiny. Through religious rituals, people cherish words to honor heaven and seek to change their destinies through heavenly forces, reflecting worldly desires and spiritual pursuits and emphasizing heaven with personhood. In contrast, the Tianli conception sees words as carriers of moral and natural laws. Guided by Confucian ethics and the concept of karma and retribution, it influences people’s moral norms and behavioral practices, reflecting the metaphysical moral law of a just and righteous heaven. Both conceptions not only involve the worship and protection of words but also profoundly embody a deep understanding and pursuit of the order of the universe, moral norms, the ethics of life, and the meaning of life. This study reveals three modes of influence: the religious philosophy integration model, the ritual practice model, and the architectural embodiment model. These models emphasize the positive impact of Xizi-belief on ethics and social life, prompting people to demonstrate positive guidance in human behavior through reverence for Tianming (mandate of heaven), adherence to Tianli (principle of heaven), and respect for nature. Under the guidance of classical religious ethical principles, the spread of Xizi-belief and the practice of Xizi religious ceremonies promote the harmonious development of individual virtues and social order, achieving harmony between humans and the universe.